2007
DOI: 10.1360/cjcp2007.20(2).173.7
|View full text |Cite
|
Sign up to set email alerts
|

Existence of Bound-Rubber in Magnetorheological Elastomers and Its Influence on Material Properties

Abstract: In efforts to develop a new fabrication method for improvement of the MREs' performance, the boundrubber phenomenon was observed in MREs. Further experiments indicate the existance of bound-rubber and it influences the MRE performance as well as the particle size. Both theoretical analysis and experimental results indicated that MRE performance can be improved by enhancing the ratio of particle radius to boundrubber thickness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…The shape of particles can also have influence on the MR effect, it is better if they have an asymmetric shape with the main axis of anisotropy [63]. Few works have reported positive effect of surface modification of particles on the growth of magnetorheological effect [68], although others show clearly that due to the better adhesion particle-matrix boundary region occurs and the ability of particles to move is reduced, which leads to a reduction of MR effect [69,70].…”
Section: The Rheological Properties and Magnetorheological Effect Of mentioning
confidence: 99%
“…The shape of particles can also have influence on the MR effect, it is better if they have an asymmetric shape with the main axis of anisotropy [63]. Few works have reported positive effect of surface modification of particles on the growth of magnetorheological effect [68], although others show clearly that due to the better adhesion particle-matrix boundary region occurs and the ability of particles to move is reduced, which leads to a reduction of MR effect [69,70].…”
Section: The Rheological Properties and Magnetorheological Effect Of mentioning
confidence: 99%
“…Gong et al [13] and Lokander and Stenberg [9] reported the advantageously influence on the MR effect of the addition of plasticizers to the silicon rubber due to the decrease of the polymer matrix stiffness. Jiang et al [14] indicate on the positive effect of the particles surface modification on the increase of the MR effect, while Zhang et al [15], Fan et al [16] and Li et al [17] show that the enhancement of the particle-polymer matrix interaction leads to the decrease of MR effect due to the existence of bound-rubber phenomenon. The improvement of filler-matrix interaction is an effective way to improve the mechanical properties of materials; however in the case of MREs it can affect the MR effect.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, at a critical stress level, debonding acts as a distinct failure phenomenon in an elastomer containing rigid inclusions, due to stress concentrations at the weak particle-matrix interface [11]. Therefore the phenomenon of debonding, bound and entrapped rubber appears as a key property for the behavior of filler-rubber compounds [12,13] and has actually been observed in MREs [14]. *tobias.possinger@cea.fr; phone +33 (0)1 69 08 02 39 Besides, the common use of silicone oil as a diluting agent to decrease the modulus of silicone elastomers tends to enhance by facilitating frictional sliding at the interfaces between the matrix and the particles [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%